Job satisfaction application, assessment, cause, and consequences - Spector, Paul E. (Thousand Oaks, Calif. ; London : SAGE, 1997)
This overview of the most studied variable in organizational behaviour research considers the nature of job satisfaction techniques for assessing job satisfaction, cultural and gender differences in job satisfaction, and more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Job satisfaction